The The Relationship Between Body Image Satisfaction and Nutritional Status in Female Students of High School - Walanda, Ryka M.; Natasya, Lulu; Harun, Haerani; Ramadhan, Muhammad Z. (Jurnal Akademika Kimia, 2025)
In the adolescent phase, there is physical, social, and psychological development and growth. These changes will affect the way adolescents view and behave towards their body, known as body image. Appearance is important for adolescent girls, so most adolescent girls try to meet society's beauty standards by fasting, dieting, exercising, taking laxatives, and diet pills. The behavior of restricting diet and living an unhealthy lifestyle can affect adolescent nutrition, such as anemia, malnutrition, and obesity. This study aims to determine the relationship between body image satisfaction and nutritional status in SMA Negeri 5 Palu students. This study uses an observational analysis method with a cross-sectional design. The sample in this study amounted to 92 respondents. The sampling technique used was proportionate stratified random sampling. The bivariate analysis test used the Spearman test. The results of the Spearman test showed a p-value = 0.097 (p>0.05), which means that there is no relationship between body image satisfaction and nutritional status in SMA Negeri 5 Palu students. There is no relationship between body image satisfaction and nutritional status in female students of SMA Negeri 5 Palu.